The impact of the Kanban model on Toyota’s agility - Hachemi , Inas; Bakhouche , Madiha (Dirassat Journal Economic Issue, 2024)
This study investigates the working mechanisms of agile organizations by exploring theoretical concepts associated with their practices and applications. The Kanban model is examined as one of the key models contributing to organizational agility, particularly in the context of Toyota’s operations. The study focuses on the implications of applying Kanban principles, including visualizing the workflow, limiting work in process, managing the flow, and pulling systems, in improving Toyota’s agility. The results show that the implementation of the Kanban model has a significant positive effect on Toyota’s agility, highlighting the model’s potential as a key driver of organizational agility.